INFORMATION DEVELOPMENT: the International Journal for Librarians, Archivists and Information Specialists, publicado por Mansell Publishing Ltd. - Tarapanoff, Kira (Revista de Biblioteconomia de Brasília, 1986)
INFORMATION DEVELOPMENT: the International Journal for Librarians, Archivists and Information Specialists. London: Mansell Publishing Ltd., v.1, n.1, Jan. 1985 — (ISSN 0266-6669).